2022
DOI: 10.1002/pits.22818
|View full text |Cite
|
Sign up to set email alerts
|

Academic procrastination using social media: A cross‐sectional study with middle school students on the buffering and moderator roles of self‐control and gender

Abstract: Temporary school lockdowns and physical distancing practices due to the Covid‐19 pandemic have led to the risk of problematic social media use (PSU) in students who need to socialize. The effect of PSU on students' academic commitment and the mechanisms that moderate this effect spark interest in researchers. For this reason, the present study sought answers to the following two research questions: (a) Whether PSU positively predicts academic procrastination (AP), (b) Whether this relation is moderated by self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 153 publications
(236 reference statements)
0
4
0
Order By: Relevance
“…Alternative behaviors to studying, such as mobile phone use or internet browsing, have also been of interest to researchers, with nine publications dedicated to exploring the relationship between academic procrastination and these types of behaviors, e.g., [ 14 , 16 , 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative behaviors to studying, such as mobile phone use or internet browsing, have also been of interest to researchers, with nine publications dedicated to exploring the relationship between academic procrastination and these types of behaviors, e.g., [ 14 , 16 , 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, researchers became interested in studying the behavior of children and adolescents during the prolonged periods of confinement due to the COVID-19 pandemic. Research in relation to procrastination focused primarily on the significant increase in the use of electronic devices and social media, as well as the procrastination of academic activities that were mandatory online during that period, e.g., [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with the Talaue et al (2018), same inference as this study who had the opinion that students who often use Facebook as well as other social media outlets perform badly in class, which is evidenced by their poor performance. Üztemur and Dinç (2023) concluded that students who used social media excessively, had to face academic procrastination. The use of social media makes them addicted, and as a result, they become lazy.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the time spent on social media and addictive behaviors may lead to procrastination in academic tasks as well as in other daily tasks (Andreassen et al, 2017; Kuss & Griffiths, 2011). Specifically, a study conducted during COVID‐19 found that problematic social media use positively affects academic procrastination (Üztemur & Dinç, 2023). Based on these findings from previous studies and the COVID‐19 pandemic context, it is reasonable to believe that BPNS may indirectly affect students' academic procrastination through social media addiction.…”
Section: The Potentially Mediating Role Of Social Media Addictionmentioning
confidence: 99%
“…We recommend collecting more homogeneous data concerning gender in future academic procrastination and social media addiction studies and including the gender variable in research hypotheses. Indeed, a recent study has revealed that the relationship between problematic social media use and academic procrastination is moderated by gender (Üztemur & Dinç, 2023). The study is cross‐sectional, and research findings do not provide causal information.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%